Smartphones-Based Assistive Technology: Accessibility Features and Apps for People with Visual Impairment, and its Usage, Challenges, and Usability Testing - Senjam SS (Dove Medical Press, 2021)
Suraj Singh Senjam,1 Souvik Manna,1 Covadonga Bascaran2 1Department of Community Ophthalmology, Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India; 2International Centre for Eye Health, Department of Clinical Research, London School of Hygiene and Tropical Medicine, London, UKCorrespondence: Suraj Singh SenjamDepartment of Community Ophthalmology, Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, IndiaEmail drsurajaiims@gmail.comAbstract: Smartphones are less likely to be considered as assistive technology for visual impairment among a large majority of health care providers, excluding vision rehabilitation professionals, and the general public who are not familiar with accessible features and apps. The present review aims to highlight accessible features and apps along with usages, including educational, and access to smartphones as assistive technology for visual impairment and blindness. It also includes advantages and challenges faced by users, and usability testing by app developers. There have been significant recent developments in mobile technology that incorporate computer technology relating to electronic information, communication, and touch-screen accessibility. Such advances in technology are transforming the use of smartphones from a traditional visual interface to a truly visual free interaction using alternative body senses, such as haptic, gesture, and so on. There are many built-in accessible features and third-party accessible applications that enable people with visual impairment to perform daily activities, independent functioning, movement, social inclusion and participation, education, etc. They are universally designed, so they are unlikely to induce social stigma or negative reactions from peers or public. Healthcare practitioners, not limiting to eye care, and caregivers, family members, teachers, or special educators should be informed about the potential uses and benefits of smartphones for visually impaired in developing nations. Evidence shows that most of the users train by themselves. Enhancing the awareness along with training for teachers and caregivers would be helpful to improve access and skills among users with visual disabilities. Developers are continuously producing more innovative applications for visual impairment, which indicates the need for having a training guideline on the use of smartphones.Keywords: assistive technology, smartphones, accessible applications, visual impairment, usage